2019
DOI: 10.17323/2500-2597.2019.1.77.89
|View full text |Cite
|
Sign up to set email alerts
|

Foresight in Higher Education Institutions: Evidence from Poland

Abstract: T he rapid transformation of the socioeconomic, political, and technological context predetermines changes in the expectations for higher education institutions which face numerous profound challenges. In order to survive and develop under changing conditions, universities need to drastically rethink their development strategies. This paper substantiates the effectiveness of using foresight for these purposes, which is confirmed by the experience of a project on the development of scenarios for the Faculty Кey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 11 publications
0
17
0
2
Order By: Relevance
“…According to Fung (2014), the typical criteria for processes suitable for RPA are: • low cognitive requirements (it is hardly possible for complex processes with many complicated tasks to be handled by RPA); • no requirement for the access to multiple systems as RPA is applied on top of existing applications; • relatively frequently performed processes and tasks are good candidates for RPA implementation; • processes with a high probability of human error and limited exceptions should be selected first for RPA. Over the last few years, digital transformation was mostly influenced by such technologies as cloud, edge computing, IoT, and AR (Gudanowska, 2017;Siderska & Jadaan, 2018;Ślusarczyk, 2018;Ejdys et al, 2019;Krykavskyy, 2019;Nosalska & Mazurek, 2019;Gudanowska & Kononiuk, 2020;Halicka, 2020). However, analytics emphasise that up to 2020, a set of such technologies will be supplemented with others that will significantly affect the digital revolution, namely, 5G, AI, advanced analytics, Machine Learning, blockchain (Hofbauer & Sangl, 2019), conversational AI, XaaS, connected vehicles, autonomous drones, and smart cities (Szpilko, 2020;Forbes, 2019;Winkowska et al, 2019).…”
Section: Rpa Characteristics Of and Its Influence On Digital Transformentioning
confidence: 99%
“…According to Fung (2014), the typical criteria for processes suitable for RPA are: • low cognitive requirements (it is hardly possible for complex processes with many complicated tasks to be handled by RPA); • no requirement for the access to multiple systems as RPA is applied on top of existing applications; • relatively frequently performed processes and tasks are good candidates for RPA implementation; • processes with a high probability of human error and limited exceptions should be selected first for RPA. Over the last few years, digital transformation was mostly influenced by such technologies as cloud, edge computing, IoT, and AR (Gudanowska, 2017;Siderska & Jadaan, 2018;Ślusarczyk, 2018;Ejdys et al, 2019;Krykavskyy, 2019;Nosalska & Mazurek, 2019;Gudanowska & Kononiuk, 2020;Halicka, 2020). However, analytics emphasise that up to 2020, a set of such technologies will be supplemented with others that will significantly affect the digital revolution, namely, 5G, AI, advanced analytics, Machine Learning, blockchain (Hofbauer & Sangl, 2019), conversational AI, XaaS, connected vehicles, autonomous drones, and smart cities (Szpilko, 2020;Forbes, 2019;Winkowska et al, 2019).…”
Section: Rpa Characteristics Of and Its Influence On Digital Transformentioning
confidence: 99%
“…Key factors identified at this stage with a high level of importance and low level of predictability and the highest degree of influence on other factors and dependencies on them may become axes of smart city scenarios. A regional project relating to the development of nanotechnology [97,99] and universities [100] in Poland constitutes an example of a description of research with the use of the STEEPVL and structural analyses.…”
Section: • Survey Researchmentioning
confidence: 99%
“…The literature review identified a research gap, which shows that the implementation of the smart city concept is poorly embedded in a multi-sphere and multi-variant vision of the future In the opinion of the authors, a tool that would enable the development of a vision of the future of a smart city with the involvement of a wide range of stakeholders forming a local community, could be foresight, which has been successfully used in building a vision of the future of countries, regions and businesses (Nazarko, 2013;Nazarko et al 2013Nazarko et al , 2015aNazarko et al , 2015bEjdys, 2014;Szpilko 2015;Ejdys et al, 2019). It, therefore, seems appropriate to develop a foresight methodology for planning the future of smart cities, in which citizens are both users and co-creators of smart cities.…”
Section: Discussionmentioning
confidence: 99%